Javanese Batik Motifs and Ornamentation as Objects of Aesthetics and Generative Art with Pseudo-Algorithm - Dewi Retno Sari Saputro; Yekti Widyaningsih; Antoni Wibowo (Javanologi: International Journal of Javanese Studies, 2023)
The batik patterns that are known to be fractal are the reality that there are alternative perspectives that exist among Indonesian society and civilization which are unique relative to the general modern perspective. This uniqueness is important considering that fractals are a form of understanding geometry and system complexity. Pseudo-algorithm in batik is an ornamentation process: klowongan-isenharmonization which starts from the smallest fractional elements of batik motifs (fractals), has selfsimilarity and is carried out through iterative computational methods. Batik as a patterned aesthetic object has pseudo-algorithmic depiction rules that can be treated as a generative art form. Batik that can be developed as fractal batik is batik with geometric motifs. Fractals have initiated a change and presented scientific creativity and progressivity in several fields in the form of interdisciplinary. All computational patterns growth to find fractal character in batik can turn into the sources of creativity to create new motifs.Keywords: Javanese batik, ornamentation, Aesthetic, pseudo algorithm